Disturbance of Ultisol soil based on interactions between furrow openers and coulters for the no-tillage system - Francetto, Tiago R.; Alonço, Airton dos S.; Brandelero, Catize; Machado, Otávio D. da C.; Veit, André A.; Carpes, Dauto P. (Spanish Journal of Agricultural Research, 2016)
The present study evaluated the effect of different associations between coulters and fertilizer furrow openers on soil disturbance, furrow depth and width, according to forward speed. The study was conducted on a farm in Santa Maria (Brazil/RS), in soil classified as sandy loam Ultisol. The experiment consisted of 24 combinations of treatments with three replications in a 2×3×4 factorial experiment. The combinations were formed by the interaction of the factors including: two types of furrow openers (hoe and double-disc), three types of coulters (no-coulter, smooth and offset fluted) and four levels of forward speed (1.11, 1.67, 2.22 and 2.78 m/s). Soil elevation and soil disturbance area profiles were obtained with the use of a micro profilometer, and disturbance values were calculated with the aid of computer software program Auto Cad. The disturbance area was not affected by speed; it was greater when using the hoe opener, and in association with the offset fluted coulter. Speed was inversely proportional to the depth of the furrows made by the hoe opener. Furthermore, the hoe caused the greatest furrow width (0.26 m) in comparison with the double-disc (0.24 m). The use of different coulters associated with furrow openers increased this variable (0.23 m for the no-coulter condition, 0.25 m with smooth and 0.26 m with offset fluted). The use of coulters combined with furrow openers reduces soil swelling, in approximately 8% for the smooth and 20% for the offset fluted.